2023
DOI: 10.1186/s13567-023-01168-8
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of a multi-type resurgence of Mycobacterium bovis in cattle and badgers in Southwest France, 2007-2019

Abstract: Although control measures to tackle bovine tuberculosis (bTB) in cattle have been successful in many parts of Europe, this disease has not been eradicated in areas where Mycobacterium bovis circulates in multi-host systems. Here we analyzed the resurgence of 11 M. bovis genotypes (defined based on spoligotyping and MIRU-VNTR) detected in 141 farms between 2007 and 2019, in an area of Southwestern France where wildlife infection was also detected from 2012 in 65 badgers. We used a spatially-explicit model to re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 71 publications
0
3
0
Order By: Relevance
“…We have also stored this package on Zenodo (https://doi.org/10.5281/zenodo.10992191; (Calenge et al 2024)). The raw dataset used in this paper has also been stored as a text file on Zenodo (https://doi.org/10.5281/zenodo.10992555; (Bouchez-Zacria et al 2024)).…”
Section: Fundingmentioning
confidence: 99%
“…We have also stored this package on Zenodo (https://doi.org/10.5281/zenodo.10992191; (Calenge et al 2024)). The raw dataset used in this paper has also been stored as a text file on Zenodo (https://doi.org/10.5281/zenodo.10992555; (Bouchez-Zacria et al 2024)).…”
Section: Fundingmentioning
confidence: 99%
“…These two processes result in the dynamics of local transmission alternating between the establishment and spillover phases. This cycle between phases can take a few years, based on another modelling study [210]. This hypothesis could provide an explanation for different patterns of transmission directions in phylodynamic studies, including a predominance of cattle-to-badger (as opposed to badger-to-cattle) transmission in some studies [25,127] and badgerto-cattle transmission in others [124,126,211].…”
Section: Insights Into Transmission Directionsmentioning
confidence: 91%
“…As a consequence of this mixing of epidemiological units in the NGM, badger vaccination efficacy would directly impact between-herd transmission, which might be an oversimplification of the challenges as described in Section 5.1. In addition, Bouchez-Zacria et al [210] estimated four partial reproduction 𝑅 0 at the herd level, by estimating transmission rate parameters (using animals as the epidemiological unit) from infection data and using simulations to aggregate herd level 𝑅. Although the epidemiological units are different from the NGM in Chapter 3, this study similarly identified high intra-species transmission (with estimated 𝑅 𝑏,𝑐 = 0.21 ∼ 1.09, 𝑅 𝑐,𝑏 = 0.38 ∼ 1.45) and low within-species transmission (𝑅 𝑐,𝑐 = 0.24 ∼ 0.74, 𝑅 𝑏,𝑏 = 0.08 ∼ 0.41), which suggests that badger-cattle could be a maintenance-community in some areas [210].…”
Section: Ngm and 𝐑mentioning
confidence: 99%